Income convergence in the asean-5 countries - Fumitaka Furuoka; Rajah Rasiah; Rafiq Idris; Patrick Ziegenhain; Ray Ikechukwu Jacob; Qaiser Munir (Universiti Malaysia Sarawak, 2018)
Mainstream economic arguments posit that liberalization is the route latecomer economies should pursue to achieve income convergence between countries. The Association of Southeast Asian Nations (ASEAN) offers a useful platform to test if trade liberalization has been accompanied by income convergence since the grouping have been among the most aggressive in promoting the removal of trade restrictions in the world. Owing to data limitations involving Brunei and the transition economies of Cambodia, Laos, Myanmar and Vietnam, the assessment is confined to the founding members, namely, Indonesia, Malaysia, the Philippines, Singapore, and Thailand. The current paper tested the income convergence hypothesis by deploying some innovative and powerful unit root tests, such as the Fourier augmented Dickey–Fuller (FADF) and the Fourier ADF with structural breaks (FADF–SB) methods. However, the results show a positive causal relationship with 10% of the two-country pairings. Sixty percent of the two-country pairings showed no causal relationship at all, while the remaining 30% produced inconclusive results. These findings suggest that other variables, such as government focus on the science, technology and innovation infrastructure to promote structural transformation may be more important than trade liberalization efforts to reduce inter-country income gaps.